Flexibility and freedom for whom? Precarity, freedom and flexibility in on-demand food delivery. (1st January 2021) - Cano, Melissa Renau; Espelt, Ricard; Morell, Mayo Fuster
Abstract : On-demand delivery platforms appropriate 'freedom' and 'flexibility' discourses with claims such as 'be your own boss' and 'work as much as you want to'. During the COVID-19 pandemic, Deliveroo updated its courier platform application with a 'free login system' in Barcelona whereby platform couriers could connect to the platform whenever, wherever, and as often as they wanted to. In this paper, we ask why the introduction of a 'free login' system generated even more precarious forms of work, by comparing workforce management systems both before and during the COVID-19 period. We argue that the reason it becomes problematic is rooted in Deliveroo's business model, which is characterised by hiring on-demand, using a piece-rate payment and exercising hard workforce control through algorithmic management.